Nine actions to successfully restore tropical agroecosystems. (November 2022) - Pashkevich, Michael David; d'Albertas, Francisco; Aryawan, Anak Agung Ketut; Buchori, Damayanti; Caliman, Jean-Pierre; Chaves, Adrian David González; Hidayat, Purnama; Kreft, Holger; Naim, Mohammad; Razafimahatratra, Appolinaire; Turner, Edgar Clive; Zemp, Delphine Clara; et al.
Abstract : Well-designed approaches to ecological restoration can benefit nature and society. This is particularly the case in tropical agroecosystems, where restoration can provide substantial socioecological benefits at relatively low costs. To successfully restore tropical agroecosystems and maximise benefits, initiatives must begin by considering 'who' should be involved in and benefit from restoration, and 'what', 'where', and 'how' restoration should occur. Based on collective experience of restoring tropical agroecosystems worldwide, we present nine actions to guide future restoration of these systems, supported by case studies that demonstrate our actions being used successfully in practice and highlighting cases where poorly designed restoration has been damaging. We call for increased restoration activity in tropical agroecosystems during the current UN Decade on Ecosystem Restoration. Highlights: Ecological restoration can enhance the complexity and functioning of degraded ecosystems and deliver socioeconomic benefits. Restoring agroecosystems in the tropics has an especially high likelihood of yielding ecological, social, and economic benefits, but only if restoration approaches are well designed. Evidence-based strategies that demonstrate how to restore tropical agroecosystems successfully and tractably are needed urgently to capitalise on the opportunities afforded by the UN Decade on Ecosystem Restoration (2021–2030). We provide nine actions to guide future restoration of tropical agroecosystems and case studies that demonstrate our actions being applied successfully.